Integrasi Nilai-Nilai Ke-islaman dalam Model Pembelajaran Matematika Terhadap Motivasi Belajar Siswa MTsN 1 Lombok Timur - Pujiani, Sri; Aswasulasikin, Aswasulasikin; Kamil, Nurdin; Wirentake, Wirentake; Yakin, Ilmanul (Lembaga Bale Literasi, 2026)
This study aims to describe the impact of integrating Islamic values into mathematics learning on improving students’ learning motivation at MTs N 1 East Lombok. The background of this research is based on the dichotomy between mathematics as a scientific discipline and religious values, which has contributed to low levels of students’ intrinsic motivation. This study employed a descriptive qualitative approach with data triangulation techniques, including observation, interviews, questionnaires, and documentation. The research subjects consisted of 30 seventh-grade students and a mathematics teacher at MTs N 1 East Lombok. The implemented learning model integrated Islamic values through structured stages, including planning and implementation based on Problem Based Learning. The results revealed a significant improvement in students’ learning motivation. The average intrinsic motivation increased from 2.86 to 4.22 (gain = 1.36), while extrinsic motivation increased from 3.16 to 4.26 (gain = 1.10). The effect size values were categorized as large (d = 1.25 for intrinsic motivation; d = 0.98 for extrinsic motivation), indicating strong practical effectiveness of the intervention. The highest improvement was observed in the indicator of awareness of learning as a form of worship. These findings indicate that the integration of Islamic values is capable of transforming students’ learning orientation from purely cognitive to meaning-oriented learning. The implications of this study highlight that mathematics learning based on the integration of religious values contributes to the development of holistic intelligence, encompassing both intellectual and spiritual dimensions